Feeling unsafe in public transportation: A profile analysis of female users in the Parisian region - Vanier, Camille (Crime prevention and community safety, 2017)
In France, half of the users feel safe in public transportation. Even though women feel less safe than men, perceptions and transportation habits may differ across women. This study explores the situations in which women feel unsafe in transit environment in the Ile-de-France, the Parisian region. Drawing from the French national victimisation survey (2010-2013), this study based on a cluster analysis distinguishes four profiles of women, depending on their individual characteristics and transportation habits. Results suggest that feeling unsafe varies depending upon users’ profiles: daily working users feel less safe early in the morning and during weekdays, whereas young women feel more unsafe at night. Less active female users tend to be less safe in crowded carriages, whereas casual users experience such feelings in deteriorated and empty carriages. The article finalises making suggestions to tackle women’s feelings of unsafety, such as raising awareness on incivilities, and improving lighting and guardianship at specific times.